UNIVERSITY AS A CENTRE OF TALENT ATTRACTION: WORKING WITH GIFTED CHILDREN - Lyubov’ V. Ovsienko; Alla A. Kaybiyaynen (Высшее образование в России)
The article describes the range of university activities focused on talented students and pupils, analyzes the experience of Kazan National Research Technological University (KNRTU) in this sphere. The main approaches, mechanisms and forms of pre-university training and career-oriented work of KNRTU are covered in the paper. The paper summarizes the practical experience and outlines the forward-looking working methods in seeking talented students, and as well presents promising ways to promote engineering professions and engineering education among the secondary school and college students.